INQUIRY-BASED ENVIRONMENTAL LITERACY TO IMPROVE ENVIRONMENTAL CHARACTER CARE OF ELEMENTARY SCHOOL STUDENT - Anita Ekantini; Ika Damayanti (Universitas Pendidikan Indonesia, 2022)
The purpose of this study was to determine the effect of inquiry-based environmental literacy used in learning on the environmental care character of third grade students at MI Al Muhsin 1. This research method uses a quantitative approach with a quasi-experimental research model. In this study, learning tools were developed in the form of lesson plans and STUDENT WORKSHEET. The instrument used in this research is a character questionnaire that cares about the environment. Data analysis using t-paired test. Based on the findings, the value of the environmental care character of the students after the treatment was higher than the environmental care character before the treatment. Based on the results of the Paired Sample t-Test statistical test, the significance value was 0.000 or sig. (2-tailed) 0.05. Thus it can be said that at the 95% confidence level, there is a significant difference in the value of the environmental care character of students before being given treatment and after being given treatment. Inquiry-based environmental literacy learning facilitates students to spread nature, recognize the ecosystem around where they live, understand the damage that occurs in the environment, and be creative with plastic waste.